FRI0448 Radiological occult sacroiliac abnormalities in asymptomatic patients with inflammatory bowel disease (IBD) might precede the development of spondyloartropathy. (23rd January 2014) - Bandinelli, F.; Terenzi, R.; Giovannini, L.; Milla, M.; Genise, S.; Biagini, S.; Annese, V.; Matucci Cerinic, M.
Abstract : Background: The involvement of sacroiliac joints (SIJ) is one of the major features of Spondyloartropathies (SpA) associated to inflammatory bowel disease (IBD) and it is well known that the early detection of SIJ inflammation is crucial to identify and treat SpA on-time. Objectives: To investigate X rays sacroiliitis in IBD patients, not presenting signs and symptoms of Spondyloarthropathy (SpA), and the differences of IBD clinical and familial variables between patients with sacroiliac (SIJ) abnormalities and without. To follow up sacroiliitis patients during 3 years, evaluating the onset of SpA inflammatory back pain (IBP). Methods: 81 patients (55 Crohn-CD- and 26 Ulcerative rettocolitis -UC) with remittent and low active IBD, froma tertiary referral centre of gastroenterology Unit, were studied with X rays of SIJ (postero-anterior and oblique scan) and scored with the New York criteria by two rheumatologists. Differences of IBD clinical variables (CD and UC, remittent and low active bowel disease, durations of symptoms, extra-intestinal involvement, patients treated with surgery and not, ESR and CRP) and familiarity (for psoriasis, IBD, celiac syndrome, SpA), between patients with SIJ X rays findings and without were investigated. At three years of follow up, we re-evaluated patients with radiological sacroiliitis for onset of chronic (>3 months) IBP, belong Berlin definition, and, finally, for ASAS criteria positivity. Results: 22/81 patients (27, 1%) showed X rays sacroiilitis at baseline. New York grade 1 and 2 was observed in 17/22 (77, 3%) and 12/22 (54, 5%) patients, respectively. X rays sacroiliac involvement did not correlate with IBD clinical and familial variables. All patients were HLA B27 negative. After 3 years of clinical evaluation, 6/22, presented episodic IBP, 1/22 presented only back morning stiffness >30 minutes (>3 months) without pain and 3/22 developed chronic (> 3 months consecutive of duration) with almost two Berlin criteria for IBP. The three patients fulfilling Berlin criteria for chronic IBP, showing SIJ bone oedema at MRI (either with gadolinium either with STIR), underwent to ASAS definition for Spa and met the indication for antiTNF alpha treatment (never assumed before for IBD). Conclusions: In IBD, occult X rays sacroiliitis in IBD might precede the onset of axial symptoms. At the moment, none clinical feature at baseline might be indentified to define those patients at risk to develop SpA. Disclosure of Interest: None Declared